Goosebumps, Monster Blood III - Stine, R. L. (New York Scholastic Inc, 1995)
Evan's plan to get back at his cousin Kermit for his practical jokes backfires and he finds himself turning into a giant.
Keywords: Horror tales -- Children's stories